Biomass production and energy balance of herbaceous and woody crops on marginal soils in the Po Valley. Issue 1 (29th February 2016) - Amaducci, Stefano; Facciotto, Gianni; Bergante, Sara; Perego, Alessia; Serra, Paolo; Ferrarini, Andrea; Chimento, Carlo
Abstract: A wealth of data and information on the cultivation of perennial biomass crops has been collected, but direct comparisons between herbaceous and woody crops are rare. The main objective of this research was to compare the biomass yield, the energy balance and the biomass quality of six perennial bioenergy crops: Populus spp., Robinia pseudoacacia, Salix spp., Arundo donax, Miscanthus × giganteus, and Panicum virgatum, grown in two marginal environments. For giant reed and switchgrass, two levels of nitrogen fertilization were applied annually (0–100 kg ha −1 ). Nitrogen fertilization did not affect biomass or energy production of giant reed; thus, it significantly reduced the energy return on investment (EROI) (from 73 to 27). In switchgrass, nitrogen fertilization significantly increased biomass production and the capacity of this crop to respond to water availability, making it a favorable option when only biomass production is a target. Net energy gain (NEG) was higher for herbaceous crops than for woody crops. In Casale, EROI calculated for poplar and willow (7, on average) was significantly lower than that of the other crops (14, on average). In Gariga, the highest EROI was calculated for miscanthus (98), followed by nonfertilized giant reed and switchgrass (82 and 73, respectively). Growing degree days10 during the cropping season had no effect on biomass production in any of the studied species, although water availability from May to August was a major factor affecting biomass yield in herbaceous crops. Overall, herbaceous crops had the highest ranking for bioenergy production due to their high biomass yield, high net energy gain (NEG), and biomass quality that renders them suitable to both biochemical and thermochemical conversion. Miscanthus in particular had the highest EROI in both locations (16 and 98, in Casale and Gariga), while giant reed had the highest NEG on the silty‐loam soil of Gariga.